Software architecture in practice - Kazman, Rick (LiveLessons., 2014)
"Software Architecture in Practice LiveLessons provides aspiring architects an overview to a broad range of methods, processes, and tools that are essential to managing the complexity of large-scale software. These LiveLessons will provide you with practical, road-tested techniques and advice to help you become a software architect."--Resource description page.